Factors associated with smoking among religious secondary schools students in a district of Selangor - Olaitan, Jinadu Lukman; Md Said, Salmiah; Ariffin, Ahmad Azuhairi (Community Health Society Malaysia, 2014)
Background: The Youth Behaviour Risk Factor Surveillance Survey (YBRFSS) 2011 in Malaysia reported the national prevalence of ever and current smoking among Form 1, 2 and 4 of government secondary school students as 9.1% and 8.7% respectively. Whereas, the prevalence of ever and current smokers among males was 17.6% and 14.6% respectively. Among females 3.9% were ever smokers while 2.0% were current smokers. This study was therefore conducted to determine the prevalence and factors associated with smoking among the religious secondary school students in a district of Selangor. Materials and Methods: A cross-sectional study was conducted among 899 students from three religious schools in the district selected using cluster sampling and self- administered questionnaire was used as instrument. Data was analyzed using chi-square and multivariate logistic regression to identify the independent factors for smoking. Results: The prevalence of ever smoking was 10.1% which was higher in males (18.6%) than females (3.9%). However, the prevalence of current smoker was only 2.9% which was also higher in males (6.2%) and than females (0.5%). The independent factors for smoking were males; age group 14-15years and 16-17 years; wanting to accept cigarette from friend; having brother who smoke and a father who smokes. Conclusion: Prevalence of ever smoker was relatively higher when compared to YBRFSS. However, the prevalence of current smoker was lower than YBRFSS. The results also highlight the importance of smoke -free family background. Efforts in smoking prevention should also be focused on modifiable factors such as peer influence.